Genomic analysis in patients with myxomatous mitral valve prolapse: current state of knowledge - Gasser, S. (BMC Cardiovasc Disord, 2018)
BACKGROUND: Myxomatous mitral valve prolapse is a common cardiac abnormality. Morbus Barlow is characterized by excess myxomatous leaflet tissue, bileaflet prolapse or billowing, chordae elongation and annular dilatation with or without calcification. Extensive myxoid degeneration with destruction of the normal three-layered leaflet tissue architecture is observed histologically in such patients. Autosomal dominant inheritance with an age and sex-dependent expression has long been recognised. This review explores the current understanding of the genetics of bileaflet prolapse, with a focus on genetic analysis and the role for echocardiographical screening of the first degree relatives of affected patients. METHODS: Systematic literature searches were performed using PubMed and Embase up to September 2017. In Disse et al.’s study (study one) first degree relatives of 25 patients with Morbus Barlow who underwent mitral valve repair were screened for bileaflet valve prolapse. In Nesta et al.’s study one family with three living generations of 43 individuals with 9 confirmed cases of MVP was screened. Genotyping was performed in four families for 344 microsatellite markers from Chromosome 1 to 16. RESULTS: In study one, autosomal dominant inheritance was shown in four pedigrees. Genome-wide linkage analysis of the most informative pedigree (24 individuals, three generations) showed a significant linkage for markers mapping to chromosome 16p. Linkage to this locus was confirmed in a second family within the same study, but was excluded in the remaining two pedigrees. In study two an autosomal dominant locus was mapped to chromosome 13. 8 of the 9 individuals affected were found to suffer from bileaflet prolapse. CONCLUSIONS: Barlow’s disease is a heritable trait but the genetic causes remain largely elusive. Ch16p11.2-p12.1 is the only locus proven to be associated with bileaflet prolapse. Locus 13.q31.3-q32.1 was shown to cause bileaflet as well as posterior leaflet prolapse. This review intends to make physicians aware of genetic causes of myxomatous mitral valve prolapse, thereby emphasising the importance of cardiological examination of first-degree relatives of patients with Morbus Barlow. Integrated and more comprehensive studies are needed for identification of genes involved in this heterogenic disease. Further genomic studies may facilitate more individualised and accurate risk assessment and may help to develop possible preventive stategies for patients in the future.